Spatial Analysis and Distribution of Leptospirosis in Yogyakarta City: A Case Study for 2022 - Daulay, Meilany Syabrina Daulay; Izza, Nurul (BKM Public Health and Community Medicine, 2024)
Purpose: Leptospirosis is a disease caused by the Leptospira bacteria. Leptospirosis is a health issue that needs to be monitored year-round and is categorized as an outbreak (KLB) in the DIY Province because it is a deadly and endemic disease. Therefore, the utilization of spatial analysis of leptospirosis is necessary to map the distribution patterns of leptospirosis cases. This study aims to map and analyze the spatial distribution of leptospirosis incidents in Yogyakarta City in 2022. Method: This research employs descriptive spatial analysis methods to identify and map the distribution of incidence rates and case fatality rates by gender in 14 sub-districts of Yogyakarta City. The study data are secondary data, specifically the leptospirosis case data for 2022 registered with the Yogyakarta City Health Office. The data are processed descriptively with the help of the R program. Results: Based on the case data and spatial visualization conducted in Yogyakarta City, there were 14 leptospirosis cases in 2022 with 2 deaths (Case Fatality Rate of 14.3%). The majority of the patients were male, with 10 cases (Incident Rate of 2.4 per 100,000 population), while there were 4 cases among females (Incident Rate of 1.0 per 100,000 population). Spatial visualization results indicate that the distribution of leptospirosis cases in Yogyakarta City is concentrated in the central part of the city, with high endemic cases in sub-districts bordering Bantul Regency, including Mergangsan Sub-district with 4 cases and 1 death among a population of 31,690 people, and Umbulharjo Sub-district with 3 cases among a population of 70,996 people. Conclusion: Further research is needed to study the social environmental factors in the two sub-districts, Mergangsan and Umbulharjo, to determine what factors may influence the occurrence of leptospirosis cases in these areas.